Understanding time-temperature characteristics in microwave cladding. (August 2020) - Singh, Bhupinder; Zafar, Sunny
Highlights: Real time-temperature characteristics of microwave clad were obtained. Comparative study was made with IR pyrometer. Critical temperature of clad powder was measured from temperature distribution. Abstract: Microwave cladding is an emerging surface modification technique. Temperature control is the key issue in any surface modification technique. In microwave cladding, non-contact temperature measurement methods are widely used; however, these methods report only the surface temperature of the susceptor. In the present study, a modified B-type thermocouple was used to measure the real time-temperature distribution while developing Ni-based clad. Formation of clad has been discussed with respect of time-temperature distribution. Effect of microwave power on heating profile was also investigated.